APPLIED CONSTRUCTION OF CONCEPTS IN POLITICAL SCIENCE BEYOND THE SEMANTIC APPROACH - Максим Володимирович Яковлєв (Вісник НЮУ імені Ярослава Мудрого: Серія: Філософія, філософія права, політологія, соціологія, 2020)
Problem settingw It has always been recognized by different scholars of social sciences that concepts are essential both to theory construction in different scientific realms as well as to applied research. A practical approach to concepts suggests that concepts, however complicated they might be, should be, in essence, boiled down to measurable indicators that, in turn, can be thoroughly studied by applying qualitative or quantitative approaches. Discussion around the nature of the concepts in social science in general and particularly in the political science brought about a number of terms to denote the concepts like «essentially contested concepts» or «nomadic concepts». In order to avoid the bothersome discussion of the meaning of concepts, a prominent American scholar of social science research methodology and international relations G. Goertz said that he preferred to define concepts implicitly through a discussion of how they could be constructed. He coined the term «semantic approach» to denote the traditional approach to concepts and his alternative approach is what this article critically analyzes in comparison to other approaches to concepts ’ studies, including the traditional ones.